PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI PADA LEMBAGA SMP IBRAHYMI 3 SUKOREJO SITUBONDO METODE TOGAF ADM - Wiwik Handayani; Muyessiroh Muyessiroh; Akhlis Munazilin (CV. Denasya Smart Publisher, 2026)
Advances in information technology have encouraged educational institutions to adopt digital systems to support academic and administrative activities. However, SMP Ibrahimy 3 Sukorejo, Situbondo, still faces limitations in data management and workflow because most operational processes are manual and not yet integrated. This situation results in inefficient information management, delayed data access, and potential inaccuracies in academic reporting. Therefore, a structured and sustainable enterprise architecture design for an integrated school information system is necessary. This research employed a qualitative case study method, applying the TOGAF ADM framework as the basis for enterprise architecture design. Data were obtained through observation, interviews, and internal school documentation. The research phases included the Preliminary Phase, Architecture Vision, Business Architecture, Information System Architecture, Technology Architecture, and Opportunities and Solutions. The results indicate that the school requires an integrated information system encompassing modules for new student admissions, learning management, grade management, financial administration, and online academic communication. The technology architecture design emphasizes the need for network infrastructure, servers, and a single authentication system to ensure secure and coordinated access to digital services. The primary output of this study is a comprehensive enterprise architecture blueprint that serves as a strategic guide for the school's phased and measurable digital transformation. With this design, the digital transformation process at SMP Ibrahimy 3 is expected to be more effective and support improvements in the quality of educational services.